Archaeal Ammonia Oxidizers Dominate in Numbers, but Bacteria Drive Gross Nitrification in N-amended Grassland Soil - Sterngren, Anna E.; Hallin, Sara; Bengtson, Per (Frontiers in Microbiology, 2015)
Both ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) play an important role in nitrification in terrestrial environments. Most often AOA outnumber AOB, but the relative contribution of AOA and AOB to nitrification rates remains unclear. The aim of this experiment was to test the hypotheses that high nitrogen availability would favor AOB and result in high gross nitrification rates, while high carbon availability would result in low nitrogen concentrations that favor the activity of AOA. The hypotheses were tested in a microcosm experiment where sugars, ammonium or amino acids were added regularly to a grassland soil for a period of 33 days. The abundance of amoA genes from AOB increased markedly in treatments that received nitrogen, suggesting that AOB were the main ammonia oxidizers here. However, AOB could not account for the entire ammonia oxidation activity observed in treatments where the soil was deficient in available nitrogen. The findings suggest that AOA are important drivers of nitrification under nitrogen-poor conditions, but that input of easily available nitrogen results in increased abundance, activity, and relative importance of AOB for gross nitrification in grassland soil.